2019
DOI: 10.1002/ldr.3468
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern and temporal trend of land degradation in the Heihe River Basin of China using local net primary production scaling

Abstract: Biophysical processes and people's livelihoods largely depend on ecosystem productivity; thus, land degradation is harmful for local sustainable development. Most previous assessments of land degradation used a comprehensive index system or trend analysis without localized benchmarks; thus, they were not fully objective. Here, we assessed the land degradation in the Heihe River Basin (HRB), China using the local net primary production (NPP) scaling (LNS) method. We improved the method by dividing land capabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…(2) Extract NPP Land degradation describes a temporary or permanent decline in land productivity (Li, Meng, et al, 2020). Vegetation productivity can act as an index reflecting land degradation or rehabilitation (Kang et al, 2020).…”
Section: Determination and Calculation Of E Land Degradation Status A...mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Extract NPP Land degradation describes a temporary or permanent decline in land productivity (Li, Meng, et al, 2020). Vegetation productivity can act as an index reflecting land degradation or rehabilitation (Kang et al, 2020).…”
Section: Determination and Calculation Of E Land Degradation Status A...mentioning
confidence: 99%
“…Previous studies assessed land degradation using remote-sensing indices of vegetation, such as FVC (Han et al, 2021), NDVI (Li, Yang, & Zhang, 2021), NPP (Li, Meng, et al, 2020) and NDVI+NPP (Kang et al, 2021). Land degradation is a comprehensive degradation process caused by various factors (Pr av alie et al, 2021).…”
Section: Functionality and Limitation In Monitoring Land Degradation ...mentioning
confidence: 99%
“…Numerous studies of the effects of soil properties on plant growth have demonstrated that revegetation is threatened by the spatial heterogeneity of soil salinization, indicating that soil conditions have a significant impact on plant growth ( Hao et al., 2010 ; Huang et al., 2019 ; Han et al., 2020 ; Wang et al., 2021a ). The distribution variability of soil properties is likely to be a critical driving force in forming vegetation distribution patterns and adaptation strategies ( Li et al., 2020 ; Zhang et al., 2020b ; Wang et al., 2021b ). Recent research found that soil nitrogen, soil phosphorus, and soil potassium concentrations in arid regions decreased significantly with increased groundwater depth, aggravating erosion ( Zhang et al., 2018 ; Huang et al., 2019 ; Wang et al., 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Land-use and land-cover change (LUCC) is the most direct manifestation of the interaction between coal mining and the natural environment [14]. The ecosystem's type, structure, and function will change with the LUCC, affecting the mining area's carbon-sequestration capacity [15,16]. Therefore, the study of how the temporal and spatial responses of land-use structures and NPP are driven by coal mining helps to reveal the processes of coal mining that affect the ecosystem, and is of great significance to balancing the relationship between resource mining and the environment.…”
Section: Introductionmentioning
confidence: 99%